Reducing cooling load and lifecycle cost for residential buildings: a case of Lahore, Pakistan - Khalid, H. (Springer Science and Business Media Deutschland GmbH, 2021)
Purpose: Buildings consume a large amount of energy for space cooling during the summer season, creating an overall sustainability concern. The upfront cost associated with sustainability repels the decision-makers to often end up adopting solutions that have huge operations and maintenance costs. Therefore, the purpose of this study is to assess the lifecycle cost (LCC) implications of optimum configurations of active and passive strategies for reducing the cooling load in buildings. Methods: Several green building active and passive strategies and technologies were assimilated and their thermal performance in a hot semi-arid climate of Lahore in Pakistan using DesignBuilder V6.1 was simulated to obtain the most optimum cooling load configuration. Furthermore, LCC is estimated, and overall efficiency is evaluated to identify the most effective space cooling configuration. Results and discussion: The results suggest that a configuration of EPS for external wall insulation, vertical louvers for external shading, 6Â mm blue HRG (low-E soft coated) + 12Â mm air space + 6Â mm clear glass for windows, polystyrene as roof insulation, cross ventilation through windows, and LED lighting system has the best performance. This is the first-of-its-kind study in the hot semi-arid climate of South Asia with the city of Lahore in Pakistan as the test case and can be generalized for places with similar conditions. The findings will help the decision-makers in selecting the most load-efficient and cost-effective green building technologies to help improve overall sustainability. Conclusion: The implementation of the proposed strategies not only aids in providing user-friendly and effective decision-making but also promotes the adoption of sustainability in buildings by leveraging the existing green building technologies to enhance the environmental and economic aspects. This is a promising approach to facilitate the spread of green building construction in developing countries. It is recommended to utilize the strategies grouped in Scenario 8 to achieve a reduced cooling load and LCC of a residential building throughout its lifecycle. Â© 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.